Latina Activists across Borders : Women's Grassroots Organizing in Mexico and Texas - Peña, Milagros, 1955- (Book collections on Project MUSE., 2007)
Compares women's organizing efforts in Mexico and in the borderlands to assess the way Latina mobilization and activism is influenced by the socio-political context in which the groups of women find themselves.